The Drosophila anterior-posterior axis is polarized by asymmetric myosin activation. - Doerflinger, H.; Zimyanin, V.; St Johnston, D. (Current Biology, 2022)
The Drosophila anterior-posterior axis is specified at mid-oogenesis when the Par-1 kinase is recruited to the posterior cortex of the oocyte, where it polarizes the microtubule cytoskeleton to define where the axis determinants, bicoid and oskar mRNAs, localize. This polarity is established in response to an unknown signal from the follicle cells, but how this occurs is unclear. Here we show that the myosin chaperone Unc-45 and non-muscle myosin II (MyoII) are required upstream of Par-1 in polarity establishment. Furthermore, the myosin regulatory light chain (MRLC) is di-phosphorylated at the oocyte posterior in response to the follicle cell signal, inducing longer pulses of myosin contractility at the posterior that may increase cortical tension. Overexpression of MRLC-T21A that cannot be di-phosphorylated or treatment with the myosin light-chain kinase inhibitor ML-7 abolishes Par-1 localization, indicating that the posterior of MRLC di-phosphorylation is essential for both polarity establishment and maintenance. Thus, asymmetric myosin activation polarizes the anterior-posterior axis by recruiting and maintaining Par-1 at the posterior cortex. This raises an intriguing parallel with anterior-posterior axis formation in C. elegans, where MyoII also acts upstream of the PAR proteins to establish polarity, but to localize the anterior PAR proteins rather than Par-1.